Platypus. (18th September 2020) - Jackson, Rob
Abstract: Enriching BioScience's role as a Forum for Integrating the Life Sciences, Arts in Science provides an occasional venue for poems, visual art, and other forms of artistic expression that explore and enliven our understanding of life. Through the contributions in this section, we hope to share with our readers the passion for nature that science inspires. This contribution is from Rob Jackson, professor, Earth System Science; Senior Fellow, Stanford Woods Institute for the Environment; and Senior Fellow, Precourt Institute for Energy, at Stanford University, in California.